An Anatomically Placed Tibial Tunnel does not Completely Surround a Simulated PCL Reconstruction Graft in the Proximal Tibia - Kim, Christopher; Baker, Dustin; Albers, Brian; Kaar, Scott G. (The Journal of Knee Surgery, 2022)
Introduction It is hypothesized that anatomic tunnel placement will create tunnels with violation of the posterior cortex and subsequently an oblique aperture that is not circumferentially surrounded by bone. In this article, we aimed to characterize posterior cruciate ligament (PCL) tibial tunnel using a three-dimensional (3D) computed tomography (CT) model.Methods Ten normal knee CTs with the patella, femur, and fibula removed were used. Simulated 11 mm PCL tibial tunnels were created at 55, 50, 45, and 40 degrees. The morphology of the posterior proximal tibial exit was examined with 3D modeling software. The length of tunnel not circumferentially covered (cortex violation) was measured to where the tibial tunnel became circumferential. The surface area and volume of the cylinder both in contact with the tibial bone and that not in contact with the tibia were determined. The percentages of the stick-out length surface area and volume not in contact with bone were calculated.Results The mean stick-out length of uncovered graft at 55, 50, 45, and 40 degrees were 26.3, 20.5, 17.3, and 12.7 mm, respectively. The mean volume of exposed graft at 55, 50, 45, and 40 degrees were 840.8, 596.2, 425.6, and 302.9 mm3, respectively. The mean percent of volume of exposed graft at 55, 50, 45, and 40 degrees were 32, 29, 25, and 24%, respectively. The mean surface of exposed graft at 55, 50, 45, and 40 degrees were 372.2, 280.4, 208.8, and 153.3 mm2, respectively. The mean percent of surface area of exposed graft at 55, 50, 45, and 40 degrees were 40, 39, 34, and 34%, respectively.Conclusion Anatomic tibial tunnel creation using standard transtibial PCL reconstruction techniques consistently risks posterior tibial cortex violation and creation of an oblique aperture posteriorly. This risk is decreased with decreasing the angle of the tibial tunnel, though the posterior cortex is still compromised with angles as low as 40 degrees. With posterior cortex violation, a surgeon should be aware that a graft within the tunnel or socket posteriorly may not be fully in contact with bone. This is especially relevant with inlay and socket techniques.
Keywords: posterior cruciate ligament; tunnel; reconstruction; computed tomography